PERANCANGAN SIGN SYSTEM MASJID RAYA SUMATERA BARAT - Muhammad Fauzan; heldi heldi (Universitas Negeri Padang, 2020)
The construction of mosques in West Sumatra shows a rapid progress, the Grand Mosque of West Sumatra has become one of the landmark in Padang City as the capital of West Sumatra Province, it is located in a strategic location in the city of Padang, nevertheless the sign system infrastructure in the mosque layout has not optimal yet, including Identification Signs, Information Signs, Direction Signs and Regulatory Signs as directions sign, for serving the activities of pilgrims whovisit the area of West Sumatra Grand Mosque. The purpose of the sign system design for the Grand Mosque of West Sumatra is targgetted to effective indoor and outdoor area, informative and communicative for the visitors. The design method is the Black Box method, which is a main design process that is located in the thinking process through free exchange of ideas and then systematically transformed. Data collection is obtained through observation, interview and documentation. The design analysis approach used is the 5W + 1H analysis. The main design of this media is identification signs, information signs, direction signs and regulatory signs. Meanwhile, the supporting media consists of umbrella, caps, prayer beads, al-quran reciting places, prayer mats, clocks, and mats / footwear.Key words : sign system, landmark, indoor, autdoor